2008
DOI: 10.1002/ange.200705998
|View full text |Cite
|
Sign up to set email alerts
|

Amine Grafting on Coordinatively Unsaturated Metal Centers of MOFs: Consequences for Catalysis and Metal Encapsulation

Abstract: Die koordinativ ungesättigten Positionen in MIL‐101, Cr3(F,OH)(H2O)2O[(O2C)‐C6H4‐(CO2)]3⋅n H2O (n≈25), mit zeotypen Riesenporen können auf anderem Weg als mesoporöse Kieselgele selektiv funktionalisiert werden. Metall‐organische Gerüste mit Ethylendiamin oder Diethylentriamin an den ungesättigten CrIII‐Positionen von MIL‐101 sind im Vergleich zur Mesophase bemerkenswert aktiv bei der Knoevenagel‐Kondensation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
217
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(226 citation statements)
references
References 65 publications
(18 reference statements)
4
217
0
5
Order By: Relevance
“…[27] The synthesis of metal-containing MOFs was successful and their efficiency in liquid-phase reaction has been largely demonstrated. [24,[28][29][30][31][32][33][34] However, as described by Proch et al, [35] one of the drawbacks of some supports (MOF-177) for the oxidation of alcohol is the sensitivity towards water, which is produced in a stoichiometric way during the oxidation process. Kuhn et al reported on a new class of material, [36][37][38][39] the covalent triazine framework (CTF), which is highly stable in water.…”
Section: Introductionmentioning
confidence: 96%
“…[27] The synthesis of metal-containing MOFs was successful and their efficiency in liquid-phase reaction has been largely demonstrated. [24,[28][29][30][31][32][33][34] However, as described by Proch et al, [35] one of the drawbacks of some supports (MOF-177) for the oxidation of alcohol is the sensitivity towards water, which is produced in a stoichiometric way during the oxidation process. Kuhn et al reported on a new class of material, [36][37][38][39] the covalent triazine framework (CTF), which is highly stable in water.…”
Section: Introductionmentioning
confidence: 96%
“…The -OH functionalized MIL-101s name MIL-101-OH was synthesized via grafting utilizing reported procedures [43,47]. Before functionalization, MIL-101 was dehydrated at 150 0 C for 12 h in a vacuum oven to generate CUSs (coordinatively unsaturated sites ).The dehydrated MIL-101 (0.6 g) was suspended in anhydrous toluene (60 mL) in a round-bottom flask equippe with a reflux condenser and a magnetic stirrer, and each of 2 mmol of ETA (Ethanolamine) was added to this suspension.…”
Section: Chemicals and Synthesis And Modification Of Adsorbentmentioning
confidence: 99%
“…In our previous work, it showed that catenated MOFs exhibit high selectivity for the separation of CH 4 /H 2 mixture [18], in which the non-bonded interactions were modeled by Lennard-Jones (LJ) potentials, and no electrostatic interactions were needed to be considered. However, for CO or CO 2 separations it is essential to take the electrostatic interactions into account.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their fascinating topologies and various potential applications in industrial technologies, the design and synthesis of MOFs has undergone tremendous development in the past decade [1 3]. According to their structural motifs, MOFs can be categorized into two types: those with non-catenated frameworks [4,5] and others with catenated ones [6,7]. In the latter additional small pores and adsorption sites are formed by the catenation of frameworks, leading to MOFs with multi-pores of different sizes that may exhibit enhanced gas adsorption and separation properties [8,9].…”
Section: Introductionmentioning
confidence: 99%